Towards Public Vaccination Data Resilience During Natural Disaster Using Blockchain-Based Decentralized Application - Sari, Riri Fitri; Herdiawan, Mokhammad Rizqi; Hamzah, Muhammad; Aljundi, Muhammad; Windiatmaja, Jauzak Hussaini (Smart City, 2022)
This paper presents a platform development plan for a public vaccination decentralized data base based on Blockchain technology. Vaccination is a medical practice that allows a human body to produce a specific antibody as a means of developing a preventive measure and reducing the risk of contracting a particular disease. Systematic vaccination data recording is an utmost important system that is required particularly during the Covid-19 pandemic. The recording mechanism should utilize the state-of-the-art information and communication technology (ICT). For faster vaccination data recording, it is common to use digital technology, making the health care process faster thus decreasing time needed for the vaccination process. Data related to medical records, i.e. vaccination data records, are essential for the continuity of care of the patients. For health professionals, medical records provide an insight on the clinical judgment being exercised at the time. The presence of a complete, up-to-date and accurate medical record including all vaccination received by a patient can make all the difference to the outcome of a treatment. Although today the digital medical records have been implemented in different traditional database, these database is still very much disintegrated and prone to the happening of natural disaster. Access to medical records will become increasingly important as medical treatments become more complicated and the increase of aging population, while disasters will likely continue to occur with regular frequency. In order to tackle the problem, we propose a blockchain-based application with decentralized storage to provide easy tracing of vaccinated people while maintaining the availability and the resilience of the data stored. Blockchain technology is applied to ensure that the data remain available and secure even during natural disaster occurrence. The decentralized application proposed in this paper is built using Hyperledger Fabric, Django, and cURL. The application is deployed in the cloud using Amazon Web Services (AWS).